(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2024)
Document falsification presents a significant challenge when presenting evidence in court. Various forms of document falsification exist, such as the falsification of marriage documents, false statements from witnesses, and forgery of signatures. This study focuses on the falsification of marriage documents. This focus is warranted due to the existing gap in the discussion of this offense within Malaysian Shariah courts, which necessitates a comprehensive study. The objectives of this study are to clarify the concept of document falsification and its position in Islamic law, analyze the legal provisions from the perspectives of fiqh and Shariah law, and conduct a case study on the falsification of marriage documents in Malaysian Shariah courts. To achieve these objectives, a qualitative approach was adopted, employing a document analysis method utilizing primary and secondary data. The data obtained is presented in the form of subthemes. This study is crucial in understanding the jurisdiction of the Shariah court when handling cases related to the forgery of marriage documents and in providing awareness to the Muslim community in Malaysia about the importance of preserving the authenticity of marriage documents for legal purposes. The findings of this study indicate that there is no specific provision for the offense of forgery in general; instead, it is prosecuted under the offense of contempt of court. For the offense of falsifying marriage documents, the offender can be sentenced under Section 38 of the Family Law Act. Based on the case study analysis, the fines imposed on offenders were found to be minimal. Therefore, the researcher suggests further research comparing the practices in Shariah courts with those in civil law in terms of handling cases of falsification of marriage documents and analyzing related legal provisions. Keywords: Documents, evidence, forgery, marriage documents, legal provisions, Malaysian syariah vourt Full text: PDF